Borderline: Reading Mark 7.24–30 as a white woman. Issue 1 (2nd January 2022) - Starr, Rachel
ABSTRACT: This article considers how to read the Bible attentive to whiteness, building on the approach proposed in David Holgate and Rachel Starr, SCM Studyguide to Biblical Hermeneutics 2nd edition (2019). Using Mark 7.24–30 as a case study, it asks how white readers might be open to confrontation and transformation in their encounters with the text. It considers how white readers need to both disassociate with the dominant character of Jesus and hear the challenge presented to Jesus by the Syrophoenician woman. It asks how Jesus' racial slur still whistles through the English West Midlands, a region marked by racism. It engages with Silvia Regina de Lima Silva's reading of the text from her experience as an African Brazilian woman ( En territorio de frontera: una lectura de Marcos 7, 24–30, 2001). In dialogue with de Lima Silva, it offers some suggestions for how white readers might read the biblical text in ways that reveal and challenge white supremacy and that contribute to the work of healing and solidarity.